Pendekatan Epsilon-Delta terhadap Konsep dan Pembuktian Limit dalam Analisis Real - Firmansyah, Ahmad Maulana (Maliki Interdisciplinary Journal, 2025)
This article aims to elaborate on function limit through the epsilon-delta approach and bridge the intuitive understanding from calculus to formal proof in real analysis. The writing of this article uses the method of literature study and conceptual analysis, by referring to standard textbooks of real analysis and relevant mathematical literature. The stages of discussion include presenting the connection between intuitive concepts and formal definitions, in-depth analysis of each component of the definition of , and concluding with a demonstration of a systematic proof framework. The article shows that the difficulties often encountered in formal proofs can be overcome through logical understanding and a two-stage process: preliminary analysis to find the right value of and formal proof for validation. The result of this discussion is a conceptual guide that confirms that mastery of the approach is a crucial competence for the successful study of advanced mathematics, particularly in real analysis.